Effectiveness of implementing a locally-developed guideline for antibiotic treatment of lower urinary tract infection in adults in Thailand - Wisutep P. (2023)
Lower urinary tract infection (UTI) is still a major concern in clinical practice, but inappropriate antibiotics are commonly prescribed in Thailand. This study aimed to develop, implement, and evaluate the effectiveness of a clinical practice guideline (CPG) for antibiotic treatment of lower UTI in adults at Siriraj Hospital which is a university hospital in Thailand. This study comprised a retrospective cohort study development phase, and a prospective cohort study implementation phase. The outcomes of treatment were compared between phases. The development and implementation phases enrolled 220 and 151 patients, respectively. The CPG compliance rate was significantly increased from 17.3% during the development phase to 43.0% during the implementation phase (p = 0.001). The rates of fluoroquinolones and cotrimoxazole use were significantly lower during implementation than during development (p < 0.001 and p = 0.027, respectively). The rates of nitrofurantoin and fosfomycin use were significantly greater during implementation than during development (p = 0.009 and p = 0.005, respectively). The overall cure rate was not significantly different between the two study phases, but implementation group patients had significantly more unfavorable prognostic factors than development phase patients. CPG-compliance group patients had a significantly higher cure rate than CPG-non-compliance group patients (p = 0.011). The cost of the initial course of antibiotics per episode was significantly higher during the implementation phase because the cost of fosfomycin is more expensive and more fosfomycin was prescribed during implementation (p = 0.047). Implementation of the locally-developed CPG was found to be effective for increasing the appropriate use of empirical antibiotics and increasing the cure rate; however, measures to improve and reinforce CPG compliance are needed.